O alçamento vocálico pretônico na cidade de Araguari-MG - Carneiro, Dayana Rúbia (2011)
The purpose of this study was to describe the raising of pretonic mid vowels the speech of the citizens of Araguari, Minas Gerais. In this linguistic community, it is common to see that pretonic mid vowels can alternate between mid-realizations [e, o] and high [i, u], respectively, in words like al[e]gria ~ al[i]gria and c[o]zinha ~ c[u]zinha. In literature, this phonological phenomenon is referred to as Vowel Raising and it is in accordance to the theoretical model of Quantitative Sociolinguistics.The data utilized was composed of 4191 instances of pretonic mid vowels (2709 realizations of the vowel /e/ and 1482 of the vowel /o/), observed in the speech of 24 subjects. In addition to the extralinguistic factors (gender, age and education), we established as linguistic factors: distance of pretonic vowel in relation to the tonic syllable, syllable structure of pretonic mid vowel (open, closed); the preceding vowel to the pretonic mid vowel; the vowel of the tonic syllable, preceding phonological context place of articulation (labial, coronal, dorsal) and manner of articulation (continuous and not continuous); following phonological context place of articulation (labial, coronal, dorsal) and manner of articulation (continuous and not continuous), and finally, nasality.The data was submitted to the GoldVarb statistic program and the results showed that vowel raising occurs between the tonic and the following vowels. It also has an important influence on the vowel raising, confirming the application of the rule in many cases, it operates in the process of reducing the articulatory difference between pretonic vowels and adjacent consonants. We have adopted the theoretical model of the Geometry of Features, proposed by Clementes and Hume (1995) to represent the rising of pretonic vowels. The raising of pretonic mid vowels was analyzed and it has been proven that it assimilates the height feature of the following segment.